Discovery of novel SecA inhibitors against "Candidatus Liberibacter asiaticus" through virtual screening and biological evaluation. (12th June 2021) - Zhang, Zhengfang; Han, Quan; Mao, Xiongxing; Liu, Jinhua; Wang, Wei; Li, Dong; Zhou, Feng; Ke, Yang; Xu, Lei; Hu, Liu
Abstract: " Candidatus Liberibacter asiaticus" ( Ca . L. asiaticus) is the causal agent of Huanglongbing disease of citrus and current study focuses on the discovery of novel small‐molecule inhibitors against SecA protein of Ca . L. asiaticus. In this study, homologous modeling was used to construct the three‐dimensional structure of SecA. Then, molecular docking‐based virtual screening and two rounds of in vitro bacteriostatic experiments were utilized to identify novel small‐molecule inhibitors of SecA. Encouragingly, 93 compounds were obtained and two of them (P684‐2850, P684‐3808) showed strong antimicrobial activities against Liberibacter crescens BT‐1 in bacteriostatic experiments. Finally, molecular dynamics simulations were employed to explore the binding modes of the receptor–ligand complexes. Results in MD simulations showed that compound P684‐3808 was relatively stable during simulation, while compound P684‐2850 left the binding pocket. Compound P684‐3808 might be suitable as a lead compound for further development of antimicrobial compounds against SecA of Ca . L. asiaticus. Abstract : Results in MD simulations showed that compound P684‐3808 was relatively stable during simulation, while compound P684‐2850 left the binding pocket. Compound P684‐3808 may be suitable as a lead compound for further development of antimicrobial compounds against SecA of Ca . L.